(untitled) (IMC Journal of Medical Science, 2019)
Background and objectives: Helminthic infestation is one of the commonest health problems in a developing country like Bangladesh. The objectives of the current study were to determine the prevalence of helminthic infestations, associated risk factors and its effects among the rural children in Bangladesh. The trend of helminthic infestation rate over time was also analyzed. Methodology: A cross-sectional study was conducted among the rural primary school children of Sreepur Upazilla of Gazipur District. The area is located about 40 km north-east of capital Dhaka. A total of 593 students aged 5-13 years were enrolled from 5 primary schools. Out of 593 children, 204 agreed to provide fecal samples. A semi-structured questionnaire was used to collect data by face to face interview method and several anthropometric measurements along with clinical examinations were also carried out. Helminth ova were detected by direct microscopy of fecal smear and floatation concentration methods. Data were analyzed using the software IBM SPSS (Version 20). Result: Out of 204, 80 (39.2%) children were infested with at least one species of helminth. Ascaris lumbricoides, Trichuris trichiura and mixed infection was 23%, 12.8% and 3.4% respectively. Overall prevalence of infection was higher among female students compared to male students (p<0.05). Living in mud-floor and thatch walled houses were significantly (p<0.05) associated with increased helminthic infestation. The risk behaviors commonly related to helminthic infestation revealed no difference between infected and non- infected groups of children. Height, weight, mid-upper arm circumference (MUAC), skin fold thickness, and waist and hip circumference of worm infested children were not significantly different from those without worm infestation. Conclusion: The results reflect that the deworming program of Sreepur Upazilla was not fully successful. Poor socio-economic condition and lack of awareness of personal hygiene played an important role in prevalence of parasite infestation. IMC J Med Sci 2019; 13(1): 004